القوة المميزة بالسرعة وعلاقتها بالأداء المهاري والخططي الهجومي للاعبي الارتكاز المتقدمين بكرة القدم - حسن, ضياء حمود مولود; صالح, احمد سلمان (Sulaimani Journal for Humanities, 2018)
Summary: To find out the force featured as fast and performance skill offensive players focal the researchers to carry out test power distinctive speed on members sample and they players focal clubs, first-class football in the central region the second set of the season in 2016 and totaling 10 players spread over the clubs participating in the Iraqi League football (Diyala Club 2, Khalis Club 2, Club Muqdadiyah 2, Gazzanah Club 2, Club Shahraban 1, country Club 1) and at the completion of the tests were recorded all matches clubs (6 matches) by one game for each team .Has been matches the recorded on (CD) (dvd) on the gentlemen experts and specialists gentlemen in football for the purpose of analyzing and evaluating performance skill offensive player focal football. After the data reached by a researcher in the form and treated statistically . The findings of the researcher that player focal relationship a significant correlation between the power distinctive as fast and variables performance offensive focal player in football.
Keywords: Characteristic speed strength; performance tactical defense; players pivot